Perceptions of Slackline Athletes in Relation to Effects on Training and Quality of Life in a COVID-19 Situation - Lagos Hernández, Roberto (2022)
The COVID-19 disease is an emerging pandemic challenge, which has physical and psychological repercussions, deteriorating the quality of life in those who have been infected and, in turn, in those who have had to live in confinement. The objective of this study is to know the perceptions of Slackline athletes regarding the effects on training and quality of life derived from the COVID-19 situation. The research is based on a cross-sectional exploratory-descriptive quantitative method. The instrument used was a self-applied survey with three dimensions; 229 people from 28 countries correctly answered it, 176 men (15 - 57 years) and 51 women (20 - 43 years), belonging to Europe, America, Asia, and Oceania. The results show that 97.8% say they have lost motivation, 60.2% declare they have poor infrastructure conditions and / or little access to their training places, 65.5% have financial problems, and 88.2 % have presented health problems, highlighting that 10% of those surveyed have been diagnosed with positive COVID-19. It is concluded that the confinement and pandemic situation has created an unfavorable environment for Slackline athletes due to the complications to carry out their training sessions, lack of access to public spaces, demotivation, loss of physical capacity, and increase in injuries.